SUSTAINABLE SAFE AND EFFICIENT WELL SERVICE PROGRAM FOR QUALITY EXECUTION - Prasetya Utama, Ramadhan
Electric submersible pump premature failure issues result to oil production deferment which led to oil sales revenue disruption, especially for a company whose concession right is limited by contractual agreement. Well service job will be executed to replace pump to return oil well back to production. It is important to design well service job in order to have efficient and safe operation, with objective to extend pump run life as long as possible and avoid recurring cost of re-entry. Well service job itself is considered low risk but high in quantity which is required to be managed very carefully in alignment of cost spending efficiency. Research is conducted to find the root causes of premature pump failure and solution. As the control parameter, safety aspect shall always be maintained during well service job. Using DMAIC (Define Measure Analyze Improve Control) framework, the problems are studied with structured thinking process from the problem definition and measuring current process outcome based on official database of tear down analysis of electric submersible pump. It is continued with analyzing root causes of premature failures and alternatives of improvement are proposed. Root causes of majority premature pump failures are observed, which are solid interference; manufacturing and assembly; power disruption; improper pump design; installation practice. Best solution for each root cause is chosen by selecting attributes important for stakeholders and calculating overall weighed score of effectiveness, applicability, and production constraint. Business solution is implemented by dividing phase of pre-execution, execution, and post-execution and assigned responsible party for each phase. Solution is also differentiated between general solution and oil well specific solution to ensure effectiveness to problem solving. New business process will be planned before implementation, and continued improvement is to be done after reviewing the outcome of implementation.